Preparation method and application of LDH nano-network assisted polyamide nanofiltration membrane
By growing LDH nanowire networks in situ on the base membrane of the nanofiltration membrane and wrapping LDH nanosheets, a multi-dimensional pore structure is formed, and interfacial polymerization is performed as a polyamide layer template to prepare an LDH nanonetwork auxiliary polyamide nanofiltration membrane, which solves the trade-off problem between permeability and selectivity of the existing nanofiltration membrane and achieves an efficient phosphorus removal effect.
Patent Information
- Application Number
- CN202510264634.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The existing nanofiltration membranes have trade-off effects in improving permeability and selectivity, making it difficult to improve both repulsion and permeability, and the interception performance of small-sized molecules is insufficient.
LDH nanowire network is grown in situ on the surface of the porous base membrane, and small-sized LDH nanosheets are suction filtered in its pores to form a multi-dimensional pore structure, which is used as a template for the polyamide layer, and an LDH nanonetwork auxiliary polyamide nanofiltration membrane is prepared by performing interfacial polymerization.
It significantly improves the phosphorus removal efficiency of the nanofiltration membrane, has a high interception rate and large water flux, which can effectively intercept the phosphorus in the water ecosystem, overcomes the trade-off effect, and improves permeability and selectivity.
Smart Images

Figure CN119746643A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of separation composite membranes, and specifically relates to a preparation method of a LDH nano-network-assisted polyamide nanofiltration membrane and application thereof. Background Art
[0002] The direct discharge of wastewater generated by human activities has caused a rapid deterioration of the aquatic ecosystem and has attracted widespread attention worldwide, among which the eutrophication of water bodies has received the most attention. The increasing phosphorus content in wastewater has caused eutrophication of lake water bodies, which in turn has induced algal blooms and destroyed the ecosystem. At present, the commonly used phosphorus removal methods include biological phosphorus removal, chemical precipitation, electrochemical method and adsorption method, but these methods have the disadvantages of huge infrastructure, low efficiency and high cost. Therefore, choosing a more economical and efficient deep phosphorus removal method is an important research direction for water source treatment. As a rapidly developing high-tech technology, membrane separation technology has been widely used in the field of water treatment. It has the characteristics of simple process, easy operation, good filterability, high efficiency and low cost.
[0003] Among various pressure-driven membranes, nanofiltration membranes can effectively filter divalent ions, multivalent ions or substances with a molecular weight greater than 200, and have broad application prospects, including water treatment and resource recovery. Nanofiltration membranes are generally composed of a porous support layer and a dense layer, in which the dense layer composed of polyamide serves as a selective functional layer and determines the separation performance of the membrane. The preparation of large-area defect-free polyamide layers is mostly carried out through interfacial polymerization. Typical interfacial polymerization reactions include the diffusion of amine monomers from water to the organic phase and the Schotten-Baumann reaction of acid chloride monomers at the interface. However, the diffusion and reaction process of amine monomers is fast and uncontrollable, which can easily lead to changes in layer thickness, resulting in uneven pore size, and cannot simultaneously improve repellency and permeability. For a long time, the research on water treatment membranes has still focused on the difficult-to-overcome trade-off effect, that is, to achieve a two-way improvement in permeability and selectivity.
[0004] Chinese patent CN113578066A discloses a method for preparing a modified nanofiltration membrane based on MXene, comprising the following steps: (1) using a polysulfone membrane as a base membrane, pre-treating it, and uniformly spraying a solution containing MXene nanosheets onto the pre-treated polysulfone membrane, and standing it after spraying to allow the water to evaporate completely; (2) pouring an aqueous solution into the base membrane obtained in step (1), pouring out the excess aqueous solution after standing, and wiping off the residual solution on the surface of the base membrane; (3) pouring an oily solution into the base membrane obtained in step (2), standing it for reaction, and taking out the obtained nanofiltration membrane; (4) soaking the nanofiltration membrane obtained in step (3) in deionized water to remove the residual reagent, thereby obtaining a modified nanofiltration membrane. However, the transmission channel of the parallel assembled two-dimensional intermediate layer of the patent is a gap connected to each other in the vertical and horizontal directions, presenting a zigzag transmission, which is extremely tortuous. It is several orders of magnitude longer than the thickness of the stacked nanosheets, which makes it limited in improving permeability.
[0005] Chinese patent CN109012187A discloses a method for in-situ growth of layered bimetallic oxide nanofiltration membrane, which belongs to the field of nanofiltration membrane separation. The steps include: pre-treating the porous base membrane to remove surface impurities; dissolving metal salts, urea and ammonium fluoride in a solvent and stirring evenly until the oil phase disappears; placing the prepared solution in a reactor, sealing and assembling the reactor; at a certain temperature, the metal ions grow in situ in the reactor to form a layered bimetallic hydroxide nanofiltration membrane on the surface of the base membrane, and then preparing the LDO composite membrane by high-temperature calcination. The nanofiltration membrane has a retention rate and flux of 99.2% and 5.4L·m for 0.1g / L chrome black T, respectively. -2 ·h -1 bar -1 The water flux of this patented membrane is still at a relatively low level among the reported nanofiltration membranes, and it only has a good retention effect on large-sized dyes - Chrome Black T, and does not have the retention performance for small-sized molecules.
[0006] Chinese patent CN111686588A discloses a composite nanofiltration membrane with a layered double metal hydroxide as a modified template and a preparation method, which relates to the field of separation membrane technology. First, the layered double metal hydroxide modified by polyphenol molecules is loaded on a supporting base membrane to form a modified supporting base membrane. Then, an interfacial polymerization reaction is carried out on the modified supporting base membrane. During the interfacial polymerization process, the loaded modified layered double metal hydroxide is conducive to forming an active separation layer with ultra-thin thickness and large effective area. This patent utilizes the hydrophilicity of LDH to form an ultra-thin active layer with a large effective area. However, the use of suction filtration to load LDH powder particles will inevitably make the surface structure of the base membrane uneven, thereby causing the formed polyamide layer to show nanoscale heterogeneity in depth distribution, and therefore, it will affect the permeability and retention rate of the composite nanofiltration membrane. Summary of the invention
[0007] In view of the deficiencies in the prior art, the problem to be solved by the present invention is: to provide a method for preparing a LDH nanonetwork-assisted polyamide nanofiltration membrane, to improve the properties of the polyamide nanofiltration membrane by means of the LDH nanonetwork, and to obtain a nanofiltration membrane with excellent filtration effect; the present invention also provides the application of the LDH nanonetwork-assisted polyamide nanofiltration membrane.
[0008] The technical solution adopted by the present invention to solve its technical problem is: The method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane of the present invention comprises the following steps: (1) Using coating to seal the porous base membrane; (2) dissolving metal ion salt, urea and ammonium fluoride in water and stirring to obtain a precursor solution, and then immersing the porous base membrane in the precursor solution to react to obtain an LDH membrane; (3) using an organic solvent to clean and soak the LDH membrane, and drying the LDH membrane to obtain a dry LDH membrane; (4) Under vacuum conditions, immersing the dried LDH membrane in a mixed aqueous solution of piperazine and LDH nanosheets, filtering, and drying to obtain an LDH mesh membrane; (5) The LDH network membrane is immersed in a hexane solution of trimesoyl chloride to carry out a polymerization reaction, and then washed and dried to obtain an LDH nanonetwork-assisted polyamide nanofiltration membrane.
[0009] in: In the step (1), the coating is glass glaze, the porous base membrane is an ultrafiltration membrane or a microfiltration membrane, the membrane material is one of aluminum oxide, titanium oxide or zirconium oxide, and the pore size of the porous base membrane is 0.1-1.0 μm.
[0010] The metal ions in the metal ion salt in step (2) include divalent metal ions and trivalent metal ions, wherein the divalent metal ions include Ni 2+ 、Zn 2+ 、Co 2+ , Cu 2+ , Ca 2+ , Mn 2+ or Mg 2+ One of the trivalent metal ions, including Cr 3+ , Fe 3+ or Al 3+ One of them.
[0011] In the step (2), the stirring time is 30-50 min, the total metal ion concentration of the precursor solution is 30-80 mmol / L, the urea concentration is 50-140 mmol / L, the ammonium fluoride concentration is 100-200 mmol / L, the reaction temperature is 110-120° C., and the reaction time is 24-36 h.
[0012] In the step (3), the organic solvent is anhydrous ethanol, the soaking time is 10-15 hours, and the drying is oven drying at 30-50°C.
[0013] In the step (4), the piperazine concentration in the mixed aqueous solution of piperazine and LDH nanosheets is 0.5-2wt.%, and the LDH nanosheet concentration is 0.025-0.1wt.%; the filtration time is 5-20min, and the drying is done at room temperature.
[0014] In the step (5), the concentration of trimesoyl chloride in the n-hexane solution of trimesoyl chloride is 0.15-0.5wt.%, the polymerization temperature is 35-65°C, the polymerization time is 15-30min, the washing is 3-5 times of washing with n-hexane solution, and the drying is carried out by air knife drying and then placing in an oven at 50-70°C for 5-20min.
[0015] The LDH nano-network-assisted polyamide nano-filtration membrane prepared by the preparation method of the LDH nano-network-assisted polyamide nano-filtration membrane is applied to the filtration of phosphorus-containing substances, comprising the following steps: (a) preparing a phosphorus-containing solution; (b) The LDH nanonetwork-assisted polyamide nanofiltration membrane is installed on the terminal filtration device to filter the phosphorus-containing solution.
[0016] The phosphorus in step (a) comprises H2PO4 - 、HPO4 2- or PO4 3- One or more of the above, the concentration of phosphorus solution is 20-1000 mgP / L.
[0017] The filtration pressure in step (b) is 0.2-0.6 MPa.
[0018] The basic principle of the present invention is: First, a hydrothermal method is used to in-situ grow an interlaced network of LDH nanowires on the surface of a porous base membrane. The porous base membrane is placed in an LDH precursor solution. At a certain temperature and pressure, an interlaced LDH nanowire network is in-situ grown on the surface of the porous base membrane, so that the LDH nanowire network completely covers the surface of the porous base membrane. At this time, the LDH nanowire network is distributed in a honeycomb shape as a whole. The structure of the LDH nanowire network will affect the morphology of the polyamide membrane. The LDH layer structure is regulated by controlling the reaction temperature, reaction time, ion species of the LDH precursor solution and the pore size of the porous membrane. Subsequently, the small-sized LDH nanosheets wrapped with piperazine monomers are filtered into the pores of the LDH nanowire network by a vacuum-assisted method. LDH nanosheets with a size smaller than the pores on the surface of the LDH nanowires can pass through the surface and deposit in the interconnected cavities, forming a multi-dimensional pore structure of longitudinal macropores and micropores, which serves as a template material for the subsequent formation of a honeycomb polyamide membrane. Hydrophilic LDH and fluoride-containing ions have hydrogen bonding, which can slow down the diffusion rate of fluoride-containing ions to the oil phase interface during interfacial polymerization, making interfacial polymerization controllable. Finally, the LDH nano-membrane was placed in a trimesoyl chloride n-hexane solution, interfacial polymerization was performed to form a nanofiltration membrane, and then immersed in a trimesoyl chloride n-hexane solution, and nano-interfacial polymerization was performed on the LDH nano-membrane to form a honeycomb LDH nano-network-assisted polyamide nanofiltration membrane.
[0019] The beneficial effects of the present invention are as follows: The present invention forms an LDH nano-network-assisted polyamide nanofiltration membrane through the porous basement membrane, the LDH nano-membrane and the polyamide layer, which can effectively intercept phosphorus in the water ecosystem. LDH grows on the surface of the porous basement membrane in the form of nanowires to form a staggered network, and piperazine-wrapped LDH nanosheets are added to the pores of the LDH nano-network to form a multi-dimensional pore structure, control the surface morphology of the polyamide layer, and increase the effective filtration area of the membrane. In the present invention, the LDH nano-membrane forms a staggered network, stores amine monomers through space and hydrogen bonding, makes the interfacial polymerization reaction controllable, and provides a porous rapid transmission channel, which significantly improves the phosphorus removal efficiency of the membrane.
[0020] The LDH nano-network-assisted polyamide nanofiltration membrane prepared by the present invention has a high rejection rate and a large water flux, is highly practical, and can effectively treat phosphorus-containing wastewater. The staggered LDH nanowire network is synthesized in situ on a porous substrate, and when in use, it can be performed without any complex equipment; the morphology and surface properties of the LDH nano-network membrane can control the uniform release of piperazine, thereby affecting the interfacial polymerization reaction, and the prepared LDH nano-network-assisted polyamide nanofiltration membrane has a special honeycomb structure, which improves the permeability and selectivity of the nanofiltration membrane. The present invention introduces nanochannels in the polyamide layer to provide additional water transport paths and reduce the packing density of the polyamide molecular chains, which can effectively overcome the trade-off effect.
[0021] The preparation steps of the invention are simple, and the obtained nanofiltration membrane has large water flux and high interception rate, can maintain long-term filtration stability, has strong practicality, and can be widely used in the field of water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the surface of the LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 1; Figure 2 This is a SEM image of the surface of the LDH composite membrane prepared in Comparative Example 1; Figure 3 This is the SEM image of the surface of the LDH composite membrane prepared in Comparative Example 2. DETAILED DESCRIPTION
[0023] The present invention is further described below with reference to the embodiments.
[0024] Example 1 (1) The Al2O3 porous ultrafiltration membrane with an outer diameter of 12 mm and a pore size of 0.5 μm was sealed with a glass glaze, and the sealing area was 11.3 cm 2 ; (2) Dissolve zinc nitrate, aluminum nitrate, urea and ammonium fluoride in water and stir to obtain a precursor solution, in which the total ion concentration of zinc nitrate and aluminum nitrate is 30 mmol / L (Zn 2+ / Al 3+ The molar ratio is 3.43), the urea concentration is 70mmol / L, the ammonium fluoride concentration is 100mmol / L, and the mixture is stirred for 30min. Then, the Al2O3 porous substrate membrane is fixed by polytetrafluoroethylene and immersed in the precursor solution, and then placed in an oven at 120℃ for hydrothermal reaction for 24h to obtain the LDH membrane. (3) The LDH membrane was cleaned with anhydrous ethanol, soaked for 12 h, and dried in an oven at 30 °C to obtain a dry LDH membrane; (4) Under vacuum conditions, the dried LDH membrane was immersed in a mixed aqueous solution of 1 wt.% piperazine and 0.025 wt.% LDH nanosheets, filtered for 5 min, and dried at room temperature to obtain an LDH nanomembrane; (5) The LDH nanomembrane was immersed in a 0.15 wt.% hexane solution of trimesoyl chloride, followed by polymerization at 65 °C for 15 min. After the reaction, it was washed three times with hexane solution, dried with an air knife, and placed in an oven and dried at 60 °C for 10 min to obtain an LDH nanomembrane-assisted polyamide nanofiltration membrane.
[0025] Example 2 (1) The Al2O3 porous base membrane with an outer diameter of 12 mm and a pore size of 0.2 μm was sealed with a glass glaze, and the sealing area was 11.3 cm 2 ; (2) Dissolve cobalt nitrate, aluminum nitrate, urea and ammonium fluoride in water and stir to obtain a precursor solution, in which the total ion concentration of cobalt nitrate and aluminum nitrate is 60 mmol / L (Co 2+ / Al 3+ The molar ratio is 3.43), the urea concentration is 140mmol / L, the ammonium fluoride concentration is 200mmol / L, and the mixture is stirred for 50min. Then, the Al2O3 porous substrate membrane is fixed by polytetrafluoroethylene and immersed in the precursor solution, and then placed in an oven at 110℃ for hydrothermal reaction for 30h to obtain the LDH membrane. (3) The LDH membrane was cleaned with anhydrous ethanol, soaked for 15 h, and dried in an oven at 50 °C to obtain a dry LDH membrane; (4) Under vacuum conditions, the dried LDH membrane was immersed in a mixed aqueous solution of 0.5 wt.% piperazine and 0.1 wt.% LDH nanosheets, filtered for 20 min, and dried at room temperature to obtain an LDH nanomembrane; (5) The LDH nanomembrane was immersed in a 0.2 wt.% benzyl chloride n-hexane solution, followed by polymerization at 35 °C for 30 min. After the reaction, it was washed 5 times with n-hexane solution, dried with an air knife and placed in an oven, and dried at 70 °C for 5 min to obtain an LDH nanomembrane-assisted polyamide nanofiltration membrane.
[0026] Example 3 (1) The Al2O3 porous base membrane with an outer diameter of 12 mm and a pore size of 1.0 μm was sealed with a glass glaze, and the sealing area was 11.3 cm 2 ; (2) Dissolve nickel nitrate, chromium nitrate, urea and ammonium fluoride in water and stir to obtain a precursor solution, in which the total ion concentration of nickel nitrate and cobalt nitrate is 80 mmol / L (Ni 2+ / Cr 3+ The molar ratio is 3.43), the urea concentration is 50mmol / L, the ammonium fluoride concentration is 110mmol / L, and the mixture is stirred for 40min. Then, the Al2O3 porous substrate membrane is fixed by polytetrafluoroethylene and immersed in the precursor solution, and then placed in an oven at 120℃ for hydrothermal reaction for 36h to obtain the LDH membrane. (3) The LDH membrane was cleaned with anhydrous ethanol, soaked for 10 h, and the LDH membrane was placed in an oven at 40 °C to dry to obtain a dry LDH membrane; (4) Under vacuum conditions, the dried LDH membrane was immersed in a mixed aqueous solution of 2 wt.% piperazine and 0.05 wt.% LDH nanosheets, filtered for 15 min, and dried at room temperature to obtain an LDH nanomembrane; (5) The LDH nanomembrane was immersed in a 0.5 wt.% benzyl chloride n-hexane solution, followed by polymerization at 55 °C for 20 min. After the reaction, it was washed three times with n-hexane solution, dried with an air knife, and placed in an oven at 50 °C for 20 min to obtain an LDH nanomembrane-assisted polyamide nanofiltration membrane.
[0027] Comparative Example 1 The LDH membrane obtained in step (3) is not immersed in a mixed aqueous solution of piperazine and LDH nanosheets, nor is it immersed in a n-hexane solution of trimesoyl chloride. The remaining steps are the same as in Example 1 to obtain an LDH composite membrane.
[0028] Comparative Example 2 No LDH nanosheets are added to the mixed aqueous solution in step (4), and the remaining steps are the same as those in Example 1 to obtain an LDH composite membrane.
[0029] Comparative Example 3 No piperazine is added to the mixed aqueous solution in step (4), and the remaining steps are the same as those in Example 1 to obtain an LDH composite membrane.
[0030] The LDH nanonetwork-assisted polyamide nanofiltration membranes prepared in Examples 1-3 and the LDH composite membranes prepared in Comparative Examples 1-3 were respectively applied to the filtration experiments of phosphorus-containing substances.
[0031] (1) Prepare 6 portions of 20 mgP / L KH2PO4 solution and set the filtration pressure to 0.2 MPa.
[0032] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 1 has a phosphorus rejection rate of 98.95% and a flux of 48.20 L·m -2 ·h -1 bar -1 .
[0033] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 2 has a phosphorus rejection rate of 97.89% and a flux of 55.92 L·m -2 ·h -1 bar -1 .
[0034] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 3 has a phosphorus rejection rate of 98.67% and a flux of 48.26 L·m -2 ·h -1 bar -1 .
[0035] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 1 was 4.57%, and the flux was 189.57 L·m -2 ·h -1 bar -1 .
[0036] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 2 was 25.73%, and the flux was 113.74 L·m -2 ·h -1 bar -1 .
[0037] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 3 was 2.42%, and the flux was 254.78 L·m -2 ·h -1 bar -1 .
[0038] (2) Prepare 6 portions of 1000 mgP / L KH2PO4 solution and set the filtration pressure to 0.6 MPa.
[0039] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 1 has a phosphorus rejection rate of 99.01% and a flux of 46.94 L·m -2 ·h -1 bar -1 .
[0040] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 2 has a phosphorus rejection rate of 97.33% and a flux of 52.75 L·m 2 ·h -1 bar -1 .
[0041] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 3 has a phosphorus rejection rate of 98.89% and a flux of 50.61 L·m -2 ·h -1 bar -1 .
[0042] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 1 was 2.64%, and the flux was 228.38 L·m -2 ·h -1 bar -1 .
[0043] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 2 was 22.38%, and the flux was 106.41 L·m -2 ·h -1 bar -1 .
[0044] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 3 was 2.97%, and the flux was 185.27 L·m -2 ·h -1 bar -1 .
[0045] (3) Prepare 6 portions of 500 mgP / L KH2PO4 solution and set the filtration pressure to 0.4 MPa.
[0046] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 1 has a phosphorus rejection rate of 97.55% and a flux of 54.13 L·m 2 ·h -1 bar -1 .
[0047] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 2 has a phosphorus rejection rate of 97.17% and a flux of 56.71 L·m -2 ·h -1 bar -1 .
[0048] The LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 3 has a phosphorus rejection rate of 97.98% and a flux of 48.63 L·m -2 ·h -1 bar -1 .
[0049] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 1 was 5.47%, and the flux was 191.41 L·m -2 ·h -1 bar -1 .
[0050] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 2 was 27.13%, and the flux was 110.63 L·m -2 ·h -1 bar -1 .
[0051] The phosphorus rejection rate of the LDH composite membrane prepared in Comparative Example 3 was 3.42%, and the flux was 231.82 L·m -2 ·h -1 bar -1 .
[0052] The SEM image of the surface of the LDH nanonetwork-assisted polyamide nanofiltration membrane prepared in Example 1 is shown in Figure 1 The SEM image of the surface of the LDH composite membrane prepared in Comparative Example 1 is shown in Figure 2 The SEM image of the surface of the LDH composite membrane prepared in Comparative Example 2 is shown in Figure 3 .
[0053] It can be seen from the above experimental data that the present invention constructs an LDH nanomembrane system through a hydrothermal method, thereby making the polymerization of the polyamide layer controllable, and the obtained LDH nanonetwork-assisted polyamide nanofiltration membrane has a higher retention rate for phosphorus-containing substances and a better interception effect, which can effectively solve the problem of excessive phosphorus-containing substances in the current water ecosystem.
Claims
1. A method for preparing a LDH nanonetwork-assisted polyamide nanofiltration membrane, characterized in that: The following steps are involved: (1) Using coating to seal the porous base membrane; (2) dissolving metal ion salt, urea and ammonium fluoride in water and stirring to obtain a precursor solution, and then immersing the porous base membrane in the precursor solution to react to obtain an LDH membrane; (3) using an organic solvent to clean and soak the LDH membrane, and drying the LDH membrane to obtain a dry LDH membrane; (4) Under vacuum conditions, immersing the dried LDH membrane in a mixed aqueous solution of piperazine and LDH nanosheets, filtering, and drying to obtain an LDH mesh membrane; (5) The LDH network membrane is immersed in a hexane solution of trimesoyl chloride to carry out a polymerization reaction, and then washed and dried to obtain an LDH nanonetwork-assisted polyamide nanofiltration membrane.
2. The method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane according to claim 1, characterized in that: In step (1), the coating is glass glaze, the porous base membrane is an ultrafiltration membrane or a microfiltration membrane, the membrane material is one of aluminum oxide, titanium oxide or zirconium oxide, and the pore size of the porous base membrane is 0.1-1.0 μm.
3. The method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane according to claim 1, characterized in that: The metal ions in the metal ion salt in step (2) include divalent metal ions and trivalent metal ions, wherein the divalent metal ions include Ni 2+ 、Zn 2+ 、Co 2+ , Cu 2+ , Ca 2+ , Mn 2+ or Mg 2+ One of the trivalent metal ions, including Cr 3+ , Fe 3+ or Al 3+ One of them.
4. The method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane according to claim 1, characterized in that: In step (2), the stirring time is 30-50 min, the total metal ion concentration of the precursor solution is 30-80 mmol / L, the urea concentration is 50-140 mmol / L, the ammonium fluoride concentration is 100-200 mmol / L, the reaction temperature is 110-120° C., and the reaction time is 24-36 h.
5. The method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane according to claim 1, characterized in that: In step (3), the organic solvent is anhydrous ethanol, the soaking time is 10-15 hours, and the drying is oven drying at 30-50°C.
6. The method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane according to claim 1, characterized in that: In step (4), the piperazine concentration in the mixed aqueous solution of piperazine and LDH nanosheets is 0.5-2wt.%, and the LDH nanosheet concentration is 0.025-0.1wt.%; the filtration time is 5-20min, and the drying is done at room temperature.
7. The method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane according to claim 1, characterized in that: In step (5), the concentration of trimesoyl chloride in the n-hexane solution of trimesoyl chloride is 0.15-0.5wt.%, the polymerization reaction temperature is 35-65°C, the polymerization reaction time is 15-30min, the washing is 3-5 times of n-hexane solution washing; the drying is carried out by air knife drying and then placing in an oven, drying at 50-70°C for 5-20min.
8. An application of an LDH nanonetwork-assisted polyamide nanofiltration membrane prepared by the method for preparing an LDH nanonetwork-assisted polyamide nanofiltration membrane according to claims 1-7, characterized in that: The LDH nano-network-assisted polyamide nanofiltration membrane is applied to the filtration of phosphorus-containing substances, comprising the following steps: (a) preparing a phosphorus-containing solution; (b) The LDH nanonetwork-assisted polyamide nanofiltration membrane is installed on the terminal filtration device to filter the phosphorus-containing solution.
9. Use of the LDH nanonetwork-assisted polyamide nanofiltration membrane prepared by the method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane according to claim 8, characterized in that: In step (a), phosphorus includes H2PO4 - 、HPO4 2- or PO4 3- One or more of the above, the concentration of phosphorus solution is 20-1000 mgP / L.
10. Use of the LDH nanonetwork-assisted polyamide nanofiltration membrane prepared by the method for preparing the LDH nanonetwork-assisted polyamide nanofiltration membrane according to claim 8, characterized in that: The filtration pressure in step (b) is 0.2-0.6 MPa.
Citation Information
Patent Citations
An in-situ growth method of a layered dual-metal oxide nanofiltration membrane
CN109012187A
Method for preparing modified nanofiltration membrane based on MXene
CN113578066A
Method for preparing ciprofloxacin sustained release nanoparticles
CN105727308A
Composite nanofiltration membrane taking layered double hydroxides as modified templates and preparation method
CN111686588A
Graphene oxide modified composite nanofiltration membrane as well as preparation method and application thereof
CN114225716A
Cited By
Advanced oxidation-nanofiltration integrated membrane as well as preparation method and application thereof
CN121466842A
Advanced oxidation-nanofiltration integrated membrane, preparation method and application thereof
CN121466842B